The girls in the picture [large type] : a novel - Benjamin, Melanie, 1962- (Center Point Large Print, 2018)
"A novel of the friendship and creative partnership between two of Hollywood's earliest female legends--screenwriter Frances Marion and superstar Mary Pickford"--